Temporary PPAT: Between Authority and Responsibility in Making Land Deeds in Indonesia - Maheswara, Mohamad Yuflih Huda; Benny Djaja (Journal of Law, Politic and Humanities, 2024)
This article will discuss the role of Temporary PPAT which held by Camat in land registration as preparation for deed making and its legal consequences. The legal basis used is Law Number 2 of 1998 on the Regulation of the Position of Land Deed Maker which has been amended through Government Regulation Number 24 of 2016 on the Regulation of the Position of Land Deed Maker. Temporary PPAT plays a role in making an authentic deed of transfer of land rights from the sale and purchase of the land in question by examining the certificate at the National Land Agency. With this obligation, the Temporary PPAT is responsible for the material and formal requirements of a deed by ensuring that the Temporary PPAT's obligations are carried out so that the parties can avoid land sale and purchase disputes. The method used is descriptive analysis with the conclusion that the position of Temporary PPAT has collided with the constitution that regulates PPAT is prohibited to be held by Civil Servants.